REHABILITATION OF PATIENTS WITH CARDIO–VASCULAR PATHOLOGY - D. V. Popovych; V. B. Koval; V. V. Shafranskyi; I. M. Salaida (Vіsnik Naukovih Doslіdžen', 2017)
Сardio-vascular diseases cause major public health problems. In Ukraine the complex of actions directed on creation of system of rehabilitation of cardio-vascular patients is an  addition  to the system of preventive and curative care. Further development require testing of continuity in the organization of medical and preventive and rehabilitation measures in patients with cardio-vascular disease.